1979
DOI: 10.1007/bf01008072
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of kinetic parameters of neutrophilic, eosinophilic, and basophilic granulocytes in human blood

Abstract: Two hematologically normal patients with glioblastoma and six patients with chronic lymphocytic leukemia received continuous 3H-thymidine infusions for 3--10 days. In autoradiographs of blood cell smears taken for 25 days or more after the beginning of 3H-thymidine administration the labeling index and the labeling intensity of granulocytes were determined. A sufficiently high labeling intensity, i.e. a sufficiently long autoradiographic exposure time was found to be critical for obtaining valid and reproducib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1
5

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 17 publications
1
38
1
5
Order By: Relevance
“…Indeed, pioneering work from Mantovani and his colleagues in the 1990s showed that many tumor-associated cytokines prolong neutrophil survival in culture 83 . In line with this, there is evidence that the half-life of circulating neutrophils is extended in cancer patients to 17 hours 84 , which may be the result of pro-survival signaling by G-CSF 20 . A longer life may give neutrophils more time to synthesize new molecules and perform additional effector functions during tumor progression.…”
Section: Neutrophil Lifespanmentioning
confidence: 64%
“…Indeed, pioneering work from Mantovani and his colleagues in the 1990s showed that many tumor-associated cytokines prolong neutrophil survival in culture 83 . In line with this, there is evidence that the half-life of circulating neutrophils is extended in cancer patients to 17 hours 84 , which may be the result of pro-survival signaling by G-CSF 20 . A longer life may give neutrophils more time to synthesize new molecules and perform additional effector functions during tumor progression.…”
Section: Neutrophil Lifespanmentioning
confidence: 64%
“…12,18 Once in the circulation, eosinophils have a half-life of about 18 hours and a mean blood transit time similar to neutrophils (26 h). 19 …”
Section: Biology Of the Eosinophilmentioning
confidence: 97%
“…Eosinophils are present in relatively low numbers in peripheral blood, usually accounting for no more than 5% of the total white blood cell count (33). They have a relatively short blood half-life of approximately 18 h (34). Migration to specific body sites, including the lungs and intestines, is mediated by eosinophil chemoattractants such as eotaxins.…”
Section: Eosinophil Differentiation Maturation Migration Activatiomentioning
confidence: 99%